Original paperTo what extent do psoriasis patients take an interest in their condition? – a pilot study - Chodorowska, Grażyna; Bryczek, Marlena; Dąbrowska-Członka, Małgorzata; Bartosińska, Joanna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2006)
Knowledge of psoriasis patients about their condition may have fundamental importance in effective control of the disease. Psoriasis is one of the most common diseases affecting 1.5-2.8% of our population, afflicting both women and men, mainly of the white race. It is characterised by chronic and recurrent course. In pathogenesis genetic background plays a great role but clinical manifestation is caused by various factors such as stress, viral and bacterial infections and some drugs. The aim of the study was an assessment of psoriasis patients’ knowledge about their condition as well as the interest they take to broaden it on account of numerous investigations which study the effect this dermatosis exerts on the patients’ self-assessment and their quality of life. The study included 104 patients treated in two medical centres: the Medical University Department of Dermatology in Lublin and the Specialist Hospital Dermatological Ward in Pulawy. All the patients completed an anonymous questionnaire which contained questions checking their knowledge of their own condition. For the respondents their doctor was the most common source of information on psoriasis (95.19%). Patients with university education significantly more often made use of professional literature and the Internet or sought the pharmacist’s counselling (p<0.05). The majority of patients gave a positive answer to the question concerning the negative effect of the disease on their relations with the community (65.75%, p<0.05). Female respondents in turn were aware of the fact that the disease might affect their offspring. As far as exacerbating factors are concerned the respondents were of the opinion that stress (43.27%) was the most common factor. The conducted study shows that sex, age, the level of patients’ education or their place of living have no influence on the level of their knowledge concerning the disease (differences statistically insignificant). Despite new and advanced therapies, psoriasis continues throughout the patient’s life; it often requires checks-up with the specialist and in some cases hospitalisation. Evaluated patient level of knowledge about psoriasis is insufficient, and therefore the need for active participation in psoriasis organisations is of great importance.